Optimising the Role of Villages as Pillars of Empowerment and Protection for Women Migrant Workers - Rahmawati, Aulia; Handayani, Heny; Nurazhar, Syakhila Keisha (KnE Social Sciences, 2025)
This research aims to find out how the village’s role in the protection of women migrant workers through collaborative efforts that have been carried out so far. This research is a qualitative study through a systematic literature review approach. The results of this study show that the non-optimal involvement of villages, especially in the governance of safe migration, has resulted in the increasing threat of women workers. The inability of the village to help provide socialization related to safe migration, and the absence of village regulations governing the protection of women workers makes it more difficult for victims’ families to make complaints. The weakness of village databases related to data on migrant workers originating from their area also results in the absence of accurate data related to migrant workers. A Migrant Worker Protection Task Force involving former migrant workers needs to be created as an active step in protecting women migrant workers. This research recommends the massive involvement of villages, especially in socialization, protection and the preparation of migrant worker databases in their respective villages.